Elevated CO2 Levels Delay Skeletal Muscle Repair by Increasing Fatty Acid Oxidation - Ceco, Ermelinda; Celli, Diego; Weinberg, Samuel; Shigemura, Masahiko; Welch, Lynn C.; Volpe, Lena; Chandel, Navdeep S.; Bharat, Ankit; Lecuona, Emilia; Sznajder, Jacob I. (Frontiers in Physiology, 2021)
Muscle dysfunction often occurs in patients with chronic obstructive pulmonary diseases (COPD) and affects ventilatory and non-ventilatory skeletal muscles. We have previously reported that hypercapnia (elevated CO2 levels) causes muscle atrophy through activation of the AMPKα2-FoxO3a-MuRF1 pathway. In the present study, we investigated the effect of normoxic hypercapnia on skeletal muscle regeneration. We found that mouse C2C12 myoblasts exposed to elevated CO2 levels had decreased fusion index compared to myoblasts exposed to normal CO2. Metabolic analyses of C2C12 myoblasts exposed to high CO2 had increased oxidative phosphorylation due to increased fatty acid oxidation. We utilized the cardiotoxin-induced muscle injury model in mice exposed to normoxia and 10% CO2 for 21 days and observe that muscle regeneration was delayed. High CO2-delayed differentiation in both mouse C2C12 myoblasts and skeletal muscle after injury, and was restored to control levels when cells or mice were treated with a carnitine palmitoyltransfearse-1 (CPT1) inhibitor. Taken together, our data suggest that hypercapnia leads to changes in the metabolic activity of skeletal muscle cells, which results in impaired muscle regeneration and recovery after injury.